An intelligent decision-making strategy based on the forecast of abnormal operating mode for iron ore sintering process. (December 2020) - Du, Sheng; Wu, Min; Chen, Luefeng; Cao, Weihua; Pedrycz, Witold
Abstract: The abnormal operating mode of the iron ore sintering process will produce sinter ore with low yield and poor quality. It is of high economic value to ensure that the sintering process runs under normal operating mode. An intelligent decision-making strategy based on the forecast of the abnormal operating mode for the iron ore sintering process is presented in this paper. First, a fuzzy rule-based model is used to construct the forecast model of operating mode, of which inputs are selected by the one-way analysis of variance. Then, an intelligent decision-making strategy for operating parameters is proposed based on the priority. Finally, experiments are performed by using the actual running data collecting from the industrial site. The originality of this study comes with establishing a fuzzy rule-based model to forecast the operating mode and designing an intelligent decision-making strategy based on priority to improve the abnormal operating mode. The result shows that the constructed forecast model of operating mode forecasts well in abnormal operating mode. The proposed intelligent decision-making strategy can effectively improve abnormal operating mode, which has a good application prospect in the iron ore sintering process. Highlights: An intelligent decision-making framework based on the forecast of abnormal operating mode is designed. A fuzzy rule-based model is used to build the forecast model of operating mode. An intelligent decision-making strategy of operating parameters based on priority is proposed.